Effect of Accelerated Thermal Ageing on the Selective Solar Thermal Harvesting Properties of Multiwall Carbon Nanotube/Nickel Oxide Nanocomposite Coatings. (3rd June 2012) - Roro, Kittessa T.; Mwakikunga, Bonex; Tile, Ngcali; Yalisi, Brian; Forbes, Andrew
Abstract : Varying amounts of dispersed multiwalled carbon nanotubes in NiO have been used to develop composites that absorb the solar energy very well but lose very little through emission. Determination of absorptance, α sol, and emissivity, ε ther, from such selective solar absorbers shows that the optimum efficiency of 71% can be attained when about 10 mg of MWCNTs are composited with NiO. One such absorber was subjected to thermal ageing tests. The performance criterion (PC) limit for passing the test when simulated for 25 years is ( − Δ α + 0.25 Δ ε ) ≤ 0.05 . It was found that the typical absorber had a PC value of −0.01. This value is much better than the passing limit. Raman spectra of the typical absorber before and after the thermal ageing test showed a reduced intensity in the D and G bands of disordered and graphitic carbon, respectively but an enhancement of the NiO bands indicating loss of carbon atoms due to thermal ageing tests. Simple equations are derived determining the proportion of carbon atoms that are lost and the proportion of carbon atoms that remains in the absorber; both of these are in agreement with the original carbon composition before the thermal ageing test. It is reported that the typical absorber will retain 63% of the carbon after 25 years.